Country case studies - Cornia, G (Oxford University Press, 1988)
Ten papers investigate how adverse economic developments, and consequent stabilization and adjustment policies, experienced by the majority of developing countries in the 1980s have affected vulnerable groups, especially children. Volume 1 contains a general analysis of the causes of deteriorating conditions for children during the 1980s and the effects of economic and other factors on their health and welfare. Contributions to this volume discuss the response of Botswana to economic recession and drought; Brazilian children and the economic crisis; social policy, poverty, and vulnerable groups in Chile; adjustment policies and programs to protect children and other vulnerable groups in Ghana; the impact of adjustment policies in Jamaica, 1973-85; economic adjustment and development in Peru; redirecting adjustment programs toward growth and the protection of the poor in the Philippines; the impact of adjustment and stabilization policies on social welfare in South Korea, 1978-85; the social impact of economic policies during the last decade in Sri Lanka; and adjustment policies and the welfare of children in Zimbabwe, 1980-85. Contributors are mainly economists, nutritionists, and development specialists. Cornia and Jolly are with UNICEF. Stewart is at Somerville College, Oxford, and Queen Elizabeth House. Index.